THE INFLUENCE OF THE QUALITY OF HUMAN RESOURCES, INTERNAL CONTROL SYSTEMS, AND ORGANIZATIONAL COMMITMENT ON THE VALUE OF GOVERNMENT FINANCIAL REPORTING INFORMATION (Study on Makassar City Government) - Ramadhan, Muhammad Syahrul; Pratiwi, Yayu Chandra (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
This study aims to determine and examine the effect of the quality of human resources internal control system and organizational commitment on the value of the government financial reporting information to the Makassar city government. Data collection uses primary data obtained from questionnaires using porrpose sampling technique. The sample in this study was the head of the finance section and 4 finance taff in 9 SKPD Makassar city with total of 45 respondents. The method used is quantitative method. The result of the questionnaire have been tested for validity and reliability, and classical assumptions have been tested in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity assumptions. Methods of data analysis using multiple linear regression techniques. Data were analyzed using SPSS version 26 . The results of this study indicate that the quality of human resources has an effect but not Significant on the information value of financial reporting then intern system has an effect on and is significant of the information value of financial reporting and organizational commitment has an effect but not significantly on the value of government financial reporting information.Keywords: Quality of Human Resources, Internal Control, System, Organizational Commitment and Information Value of Financial Reporting